Portuguese cultural standards from a Korean perspective - Poim, Mónica Cristina Teixeira (2021)
The main goal of this thesis is the identification of Portuguese Cultural Standards from the perspective of the South Korean Culture. To identify these, the Cultural Standards method, a still recent method to cultural difference identification was used, this method starts with by interviewing people with some life experience in a culture that is not their own. This methodology takes a qualitative approach and tries to identify cultural differences on a subtler level than other methods, like for example, Cultural Dimensions. This investigation is comprised of three phases: narrative interviews with fifteen Koreans, with living experience in Portugal of one year minimum; analysis of the interview content and identification of the critical incidents detailed during those and lastly, identification of the Cultural Standards. The Cultural Standards are the ones mentioned by several interviewees with more frequency and confirmed through feedback provided by the interviewees and additionally by two other people, non-participants in the interviews. The Portuguese Cultural Standards from a Korean Perspective identified during the interviews are: Slow Life Rhythm, Food Culture, Relaxed Lifestyle, Relevance of Relationships, Technological Efficiency and Out of Touch with the World.